Incorporating online reference in teaching photographic education for photography students / Wan Nor Ayuni Wan Mohd Zain - Wan Mohd Zain, Wan Nor Ayuni (2008)
In a visual world where messages are often carried by visual means, our attitude towards photography is changing to accepting the potential of the beyond its factuality. The challenge facing photography instruction today, is teaching photographers to be visually literate. The goal is to introduce a theoretical element within practical photography instruction which will enable students to gain the skills of visual literacy - ‘reading’ photographs in addition to ‘writing’ them. This research present a mechanism in which the online reference and instruction is not aimed to replace the traditional on campus activities but to enhance toward the effectiveness for teaching photography, that would not have been possible to achieve because of the class time limitations and the nature of the courses. The online reference model is aimed incorporate theoretical layer which would develop student’s digest and understanding for better learning situations, further on to increase compentencies becoming professional photographic practitioners. Using a case study design, I gathered data using written questionnaire, oral questionnaire (interview) and in-class observation. Students were study in ‘History of Photography’ subject from two universities at Klang Valley and Malacca has been selected. The research examines the process of teaching and learning while using an online reference in photography education. Additionally, I interviewed the lecturer about experience in using online reference and observe the class when her teaching the history subject. The result of data collection shows that student groups at two selected universities using online reference to seek information about History of photography.Based on student’s feedback; internet helped them to increase their understanding, more knowledgeable and be motivated. The lecturers agreed that this medium was helpful in prepare teaching content and save their time. Finally, Blended teaching approach of the combination between the traditional face-to-face teaching, library research and online reference is very effectual in ensuring effective teaching and learning process. Face-to-face teaching and its library research contemporary is deemed to be the traditional approach in education circle, and some educators may have viewed it as passe or out of date. Through this study it is conclude that this approach is still a very relevant approach in institutions of higher learning because of its strength in interpersonal relationship and knowledge.